Application of Remote Sensing Images for Analysis of Coastline Changes - Harpreet Kaur A/P Dalgit Singh, Harpreet Kaur (Universiti Teknologi Petronas, 2010)
Coastline changes along 4 km stretch of Terengganu coastline, Peninsular Malaysia, has been detected by simple application of satellite images and the changes are related computationally to the environmental factors. The coastline stretch, near Sungai Besut, is formed by a fairly straight shoreline but is interrupted along 400 m by a river mouth.